Generation of material‐specific energy deposition kernels for kilovoltage x‐ray dose calculations. Issue 9 (20th July 2021) - Heidarloo, Nematollah; Aghamiri, Seyed Mahmoud Reza; Saghamanesh, Somayeh; Azma, Zohreh; Alaei, Parham
Abstract: Purpose: Dose calculation of kilovoltage x rays used in Image‐Guided Radiotherapy has been investigated in recent years using various methods. Among these methods are model‐based ones that suffer from inaccuracies in high‐density materials and at interfaces when used in the kilovoltage energy range. The main reason for this is the use of water energy deposition kernels and simplifications employed such as density scaling in heterogeneous media. The purpose of this study was to produce and characterize material‐specific energy deposition kernels, which could be used for dose calculations in this energy range. These kernels will also have utility in dose calculations in superficial radiation therapy and orthovoltage beams utilized in small animal irradiators. Methods: Water energy deposition kernels with various resolutions; and high‐resolution, material‐specific energy deposition kernels were generated in the energy range of 10–150 kVp, using the EGSnrc Monte Carlo toolkit. The generated energy deposition kernels were further characterized by calculating the effective depth of penetration, the effective radial distance, and the effective lateral distance. A simple benchmarking of the kernels against Monte Caro calculations has also been performed. Results: There was good agreement with previously reported water kernels, as well as between kernels with different resolution. The evaluation of effective depth of penetration, and radial and laterals distances, defines the relationship between energy, material density, and the shape of the material‐specific kernels. The shape of these kernels becomes more forwardly scattered as the energy and material density are increased. The comparison of the dose calculated using the kernels with Monte Carlo provides acceptable results. Conclusions: Water and material‐specific energy deposition kernels in the kilovoltage energy range have been generated, characterized, and compared to previous work. These kernels will have utility in dose calculations in this energy range once algorithms capable of employing them are fully developed.